Understanding Follicular Output Rate (FORT) and its Implications for POSEIDON Criteria - Grynberg, Michael; Labrosse, Julie (Frontiers in Endocrinology, 2019)
The management of low prognosis patients in ART represents a challenge for reproductive specialists. Different profiles and biologic characteristics have been identified among these patients. Indeed, while poor ovarian response can be seen in patients with impaired ovarian reserve, others, identified as hypo-responders, show unexpected poor or suboptimal response to controlled ovarian stimulation despite satisfying ovarian parameters. These hypo-responders are associated during FSH stimulation to slow initial responses in terms of estradiol levels and follicle growth, longer stimulations, and/or greater cumulative FSH doses. Hence, it appears that ovarian sensitivity to gonadotropins differs from a patient to another, and plays a determinant role on ovarian response to stimulation. Although precise mechanisms remain to be elucidated, increasing evidence suggests that ovarian sensitivity to FSH could be influenced by the presence of genetic mutations or single nucleotide polymorphisms of gonadotropins and their receptors. Evaluating ovarian sensitivity to FSH therefore appears as a key element to improve IVF success rates in these low prognosis patients and open new treatment perspectives. Since the traditional ovarian markers currently used are not sufficient to accurately reflect ovarian response to FSH, a tool to assess ovarian sensitivity to gonadotropin stimulation was required. The present review aims to present Follicular Output Rate (FORT) as an efficient quantitative and qualitative marker of ovarian responsiveness to gonadotropins, discuss the underlying mechanisms of impaired sensitivity to FSH and the possible FORT implications for Poseidon criteria.